Analysis of current state and choice of raw material of secondary cadmium technology - Козуб, Светлана Николаевна (Technology audit and production reserves, 2015)
It is considered the main sources of raw materials and final products containing cadmium. It is shown that in most case, they have unique properties and in the near future can’t be changed without damage to other industries. It is conducted analysis of the production volumes of products containing cadmium and it is shown that in the near future is expected to decline in the production of such products. It is determined that more than 80 % of the cadmium can be re-used, and the main group of raw material of secondary cadmium technology are household nickel-cadmium current sources containing up to 30 % by weight of cadmium. It is proposed as the main raw material of secondary cadmium technology uses a small nickel-cadmium power sources. According to the analysis it is concluded that the development of technology for recycling of household nickel-cadmium batteries is promising both in terms of environmental protection, as well as from an economic point of view, as it will contribute to the development of safer and more efficient technologies for the use of cadmium in place of their ban.